Model of adsorption heat pump – Dubinin-Astakhov and Toth adsorption equilibrium comparison - Zwarycz-Makles, Katarzyna (Instal, 2020)
In the presented paper the adsorber analytical modeling results based on Dubinin-Astakhov adsorption equilibrium and Toth adsorption equilibrium of water vapour on silica gel were compared. The adsorption heat pump with silica gel adsorbent and water adsorbate was discussed. A conventional single stage cycle adsorption heat pump is modeled. The design of the adsorber/desorber considered element is the tube with deposited silica gel bed. The analytical model was created to describe the temperature and concentration changes in the adsorber/desorber and consequently to describe the performance of the adsorption heat pump. The mathematical model was solved using common spreadsheet. A considerable increase in the calculated SHP and SCP in the model based on the Toth equilibrium equation as well as slight increase in the heat supplied or released from adsorbent influenced the increase in the COP.
Keywords: adsorption heat pump; adsorption; desorption; adsorption modeling